Elucidating the mechanism of baicalein-rich fraction from oroxylum indicum leaves in cervical cancer cell lines - Wahab, Nurul Hidayah (2020)
Oroxylum indicum (O. indicum) has been implicated as a promising anticancer agent for cancer treatment including cervical cancer. Previous studies have shown that this plant has been able to inhibit the proliferation of cancer cells by acting as an apoptosis inducer. The therapeutic anti-cancer properties of O. indicum is strongly associated due to its major chemical constituents such as chrysin, oroxylin A and baicalein. In this present study, the baicalein-rich fraction (BRF) from O. indicum leaves has been extracted to elucidate its anti-cancer activity against cervical cancer cells, SiHa (HPV 16 positive) and HeLa (HPV 18 positive) cells. Using the preparative thin layer chromatography (PTLC) (n-hexane: ethyl acetate; 50:50), this fraction was prepared from the methanol crude extract (MCE) of O. indicum and proceeded to high performance liquid chromatography (HPLC) for baicalein quantification. At first, anti-proliferative activities of BRF were tested using methylene blue assay (MBA). Then, the pro-apoptotic activity of BRF in modulating protein expression was determined by Western blot analysis on the expression of HPV oncoproteins (E6 and E7), tumour suppressor proteins (p53 and pRb) and key proteins of mitochondrial signalling apoptosis pathway (Bax, Bcl-2, caspase-9 and caspase-3). Next, the dependency of BRF-induced apoptosis in cervical cancer cells to mitogen-activated protein kinase (MAPK) subfamilies consisting of extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK) and p38 were also determined by Western blot analysis with the addition of specific MAPK inhibitors. Moreover, the pro-apoptotic activity of BRF continued to be examined through its modulation action on the expression of interleukin (IL)-6 and IL-12 by conducting an enzyme-linked immunosorbent assay (ELISA). As a result, BRF with 75% of baicalein was found to be the most potent compound compared to cisplatin (anticancer drug) and MCE based on the IC50 values obtained from both cells. After 24 hours treatment period, Western blot analysis showed that BRF-treated SiHa and HeLa cells downregulated the expression of E6 and E7 and restored the induction of apoptosis process through the up-regulation of p53 and pRb in treated cells. In terms of mitochondrial-mediated apoptosis pathway, BRF has positively enhanced the activation pathway by downregulating Bcl-2 anti-apoptotic protein and upregulating the required key components such as Bax, caspase-9 as well as caspase-3. In regard to MAPK signalling cascade, the pro-apoptotic activities of BRF in SiHa and HeLa cells have been found to be MAPK-dependent as all its subfamilies involved in BRFinduced apoptosis but in different approach. BRF induced apoptosis in cervical cancer cells predominantly through ERK inhibition and JNK activation. Besides, BRF induced Bax activation by ERK/p38 dependent pathway and suppressed Bcl-2 expression through inhibition of ERK and activation of p38. Meanwhile for HeLa cells, activation of ERK/JNK/p38 pathways are required for Bax activation and inhibition of both ERK/p38 signalling promoted Bcl-2 downregulation in BRFtreated HeLa cells. Apoptosis induction by BRF also enhanced through IL-6 downregulation and IL-12 upregulation. Thus, these presented findings have proved the ability of BRF fractionated from O. indicum’s leaves to be exploited as a potential plant-based anti-cancer candidate for cervical cancer treatment.